1994
DOI: 10.1111/j.1574-6968.1994.tb07144.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ribotyping, pulsed-field gel electrophoresis and random amplified polymorphic DNA for typingClostridium difficilestrains

Abstract: Clostridium difficile is a Gram-positive sporulating anaerobic bacillus which causes pseudomembranous colitis. Nosocomial acquisition of this bacteria has proved frequent, and epidemiological markers are needed to recognize and control common-source outbreaks. We therefore compared the results of pulsed-field gel electrophoresis (PFGE) after restriction with SmaI or NruI, random-amplified polymorphic DNA (RAPD) using 3 10-mer oligonucleotides, and ribotyping to differentiate between 30 unrelated strains of C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 30 publications
4
37
0
Order By: Relevance
“…1998) where RT and RAPD analysis have generally been found to correlate with each other. However, our results are in agreement with those of Chachaty et al . (1994) who found that, although clusters of Clostridium difficile identified by RT and RAPD analysis were similar, the relative distances between clusters differed for these two methods.…”
Section: Discussionsupporting
confidence: 94%
“…1998) where RT and RAPD analysis have generally been found to correlate with each other. However, our results are in agreement with those of Chachaty et al . (1994) who found that, although clusters of Clostridium difficile identified by RT and RAPD analysis were similar, the relative distances between clusters differed for these two methods.…”
Section: Discussionsupporting
confidence: 94%
“…expected, RS-PCR fingerprinting was slightly more reproducible than AP-PCR, given the high degree of susceptibility of the latter procedure to variations in testing conditions (9). Nevertheless, the reproducibility of AP-PCR was adequate, and this relatively straightforward technique had a high degree of discrimination.…”
Section: Vol 43 2005 Molecular Epidemiology Of Endemic C Difficilementioning
confidence: 99%
“…Despite this, accessibility, in addition to time and cost restraints, means that MLVA is still not widely utilized. Random amplification of polymorphic DNA (RAPD) PCR is a quick, cost-effective method which has previously been used to characterize C. difficile isolates (Barbut et al, 1994;Chachaty et al, 1994;van Dijck et al, 1996). The method is often criticized, however, due to lack of reproducibility (Brazier, 1998).…”
Section: Introductionmentioning
confidence: 99%